The Morpho-Syntactic Properties of Anaphors in Kisukuma - Musa, Thereza; Kahigi, Kulikoyela; Mpobela, Lea (International Journal of Culture and History, 2023)
This paper focuses on the morphological and syntactic properties of anaphors in Kisukuma, a Bantu language spoken mainly in Shinyanga, Mwanza, Simiyu and Geita regions in the south eastern part of Lake Victoria by the people who call themselves βasukuma. The study was guided by three modules of Government and Binding Theory namely: Binding Theory, Government Theory and Case Theory. Qualitative research approach was employed. Data were collected through sentence questionnaires and grammaticality judgments. Four respondents who are native speakers of Kimunakiiya dialect were selected from Isoso and Ndoleleji villages by using snowball sampling basing on their age and language proficiency. The study found that anaphors in Kisukuma exist in two forms: Verbal anaphors and Nominal anaphors. Anaphors in verbal form are expressed by a single form (morph-i-) that plays one role at a time. Intrinsically the form seems to be polysemic in nature, because in addition to encoding reflexive and reciprocal events, the form is also used to encode other interpretations such as anticausative, decomitative, derogatory, chained action, asymmetric reciprocal, pretense and lack of reason. Hence the form evokes some sort of ambiguities which are solved by the number of participants, the intrinsic characteristics of a verb used and the social context which help to determine the intended meaning. Anaphors in nominal form are expressed by distinct linguistic expressions such as iyene/ng’wenekele/bhenekele ‘myself/themselves’ for reflexive and bhoyigubhoyi/iseguise ‘each other/one another’ for reciprocal interpretation. Morphologically the morph-i- is realized as a prefix attached between the TAM and verb root by the affixation process. Overtly the morph does not show agreement with its antecedent in terms of person, gender and number though covertly it acquires all the features from the overt NP via SM. Syntactically the RFM/RCM is an internal argument of the verb to which it attaches. Also, the form is a valence-reducing element that derives a transitive verb into an intransitive one, (unaccusative verb). Moreover; anaphors in Kisukuma co-refers with the whole NP via the SM to establish binding relation.